Gene Mutations in 21 Unrelated Cases of Phenotypic Heterozygous Protein C Deficiency and Thrombosis - Ireland, H; Thompson, E; Lane, D A; Protein C Study Group (Thrombosis and Haemostasis, 1996)
Mutations have been identified in the protein C gene in 21 patients with venous thromboembolism and phenotypic heterozygous protein C deficiency. In 20 probands, single mutations were the only abnormalities identified by sequencing all coding regions, intron exon boundaries and the promoter region back to -1540. In one proband 2 mutations were identified and in another family 2 mutations were identified (but not both in the proband). Of the 23 mutations, 18 resulted in predicted amino acid substitutions, 3 were mutations resulting in stop codons, one was a mutation within a consensus splice sequence and another a 9 base pair insertion within exon 5 (this region within exon 5 is proposed as a deletion/insertion hot spot). A novel polymorphism was also, uniquely, identified in the propeptide region of the molecule (Pro-21 Pro; CCT to CCC) in a kindred from Hong Kong. Cosegregation of the protein C gene mutation with protein C deficiency could be determined in 13 families. In a further family, phenotypic protein C deficiency and the genetic mutation cosegregated in only 4/5 members.The first thrombotic incident occurred in the probands between the ages of 11 and 59 years and 12 individuals suffered recurrent thrombosis. Thrombosis occurred in at least one other family member in 9/21 families, but in 2 of these it was inconsistently associated with protein C deficiency. An independent genetic risk factor, factor V Arg506Gln (FV Leiden) was identified in 2 probands (and 3 family members) and in 4 protein C deficient members of a third family but not in the proband. The results suggest that in the majority of probands with thrombosis and phenotypic protein C deficiency, a single protein C gene mutation is associated with thrombosis. However, it is also possible that additional unknown genetic risk factors contribute to the thrombotic risk. An added, acquired, risk factor leads to thrombosis at an early age (< 25 years).